Reframing Muslim Identity: Representation and Power in Islamic Diasporic Narratives - Amir Al-Azraki (Indonesian Journal of Islamic Literature and Muslim Society, 2024)
Muslim authors who depict Islam or Muslim societies in a critical light are frequently accused by fellow Muslim critics of being cultural intermediaries (compradors) who perpetuate neo-Orientalist narratives and reinforce negative stereotypes of Muslims in Western discourse. This study examines how Islam and Muslim identities are represented in four key diasporic works, Husain’s The Islamist, Yassin-Kassab’s the Road from Damascus, Aslam’s Maps for Lost Lovers, and Moaveni’s Lipstick Jihad. By analyzing these texts, the paper explores the ethical and intellectual responsibilities of Muslim writers when revealing uncomfortable or contentious “truths” about their own communities. Across these narratives, Islam is frequently portrayed as a repressive system, whether in state forms such as Saudi Arabia and Iran, or within conservative diasporic contexts, such as Muslim communities in the United Kingdom. Through a comparative analysis, this paper interrogates whether these self-critical Muslim voices, articulated through both memoir and fiction, inadvertently reinforce hegemonic Western discourses that stereotype Muslims, or alternatively, whether they contribute to a more nuanced understanding of Islam’s diversity and the multifaceted experiences of Muslims in global contexts.